2017
DOI: 10.3390/ijerph15010052
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Acinetobacter spp. Isolates from the River Danube: Susceptibility Stays High

Abstract: Acinetobacter spp. occur naturally in many different habitats, including food, soil, and surface waters. In clinical settings, Acinetobacter poses an increasing health problem, causing infections with limited to no antibiotic therapeutic options left. The presence of human generated multidrug resistant strains is well documented but the extent to how widely they are distributed within the Acinetobacter population is unknown. In this study, Acinetobacter spp. were isolated from water samples at 14 sites of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…We observed the domination of Acinetobacter sp. in contract with the previous findings ( Kittinger et al, 2017 ), reporting Acinetobacter sp., as in higher prevalence with antibiotic resistance in freshwater bodies of Austria. The 16S rRNA nucleotide sequences of bacterial isolates showed 99–100% homology with previously submitted clinical and environmental isolates indicating that bacteria in this study might have originated from domestic sewage and or hospital effluent.…”
Section: Discussionsupporting
confidence: 92%
“…We observed the domination of Acinetobacter sp. in contract with the previous findings ( Kittinger et al, 2017 ), reporting Acinetobacter sp., as in higher prevalence with antibiotic resistance in freshwater bodies of Austria. The 16S rRNA nucleotide sequences of bacterial isolates showed 99–100% homology with previously submitted clinical and environmental isolates indicating that bacteria in this study might have originated from domestic sewage and or hospital effluent.…”
Section: Discussionsupporting
confidence: 92%
“…The multidrug-resistance (MDR) status of seven clinically relevant species (Figure 2) of the isolates was evaluated and varied between 3.8% of a respective species ( A. baumannii complex) to 100% ( C. freundii, E. cloacae, E. coli, K. oxytoca , and K. pneumoniae , Figure 2). The low number of MDR A. baumannii is concordant to data from Austria (Kittinger et al, 2017) where only 4.4% of the A. baumannii isolates were MDR. These MDR-isolates were mostly third generation cephalosporin resistant, but also Carbapenem non-susceptible isolates were present within the characterized isolates ( n = 7) including two isolates of P. aeruginosa (9w-9, 10w-5), A. baumannii complex (6w-8, 8s-4), K. oxytoca (11w-2, 12w-10) and one E. cloacae complex isolate (12w-5) (Supplementary Table S4).…”
Section: Resultssupporting
confidence: 83%
“…One study found the abundance of tetracycline-resistant and fluoroquinolone-resistant bacteria to increase in river water samples further downstream [103]. Multi-drug resistant opportunistic bacteria carrying genes resistant to carbapenem, a last-resort antibiotic, have also been found in surface waters such as ponds, lakes, and rivers, representing a major challenge to public health [84,104,105]. The concentrations of ARBs and ARGs are usually higher at the point of effluent discharges from WWTWP but gradually become reduced downstream from the discharge point [106,107].…”
Section: Antibiotics Arb and Arg In Water Wastewater And Sewage Smentioning
confidence: 99%